METODE IQRO’ TERHADAP KEMAMPUAN MEMBACA HURUF HIJAIYYAH ANAK AUTIS - SULISTYA, MEDA (Jurnal Pendidikan Khusus, 2016)
ABSTRACTThe autistic disorder has effects as the obstacle in linguistic development especially in listening, speaking, reading and writing skills. In this research, the Iqro’ method is implemented to increase the result of the study in reading hijaiyyah letters of the autistic children. The purpose of this study is to analyze the hijaiyyah reading skill of the autistic children before and after the intervention using Iqro’ method. The period that is used in this research is 12 meetings with 10 times of intervention. The design that is used is one group pre-test post-test design with six children as subjects. The methods that are used are tests and documentation. The data analysis is non-parametric statistic analysis which using sign test. The result of the study shows that Z count is 2.05, and Z table in significant 5% for the two-side test (Zt=1.96). It makes Ho is rejected (2.05>1.96). According to that explanation, it can be concluded that there is a significant effect of the Iqro’ method to the hijaiyyah reading skill of the autistic students in SLB ABC Putra Harapan Kademangan Blitar.Keywords: Iqro’ method, letters reading ability, hijaiyyah